Amphibians in Eurasian otter Lutra lutra diet: osteological identification unveils hidden prey richness and male‐biased predation on anurans. (8th May 2019) - Smiroldo, Giorgio; Villa, Andrea; Tremolada, Paolo; Gariano, Pasquale; Balestrieri, Alessandro; Delfino, Massimo
Abstract: Amphibians form a major component of the diet of the otter Lutra lutra in several areas of its wide geographic range. Yet, amphibian remains are rarely identified to species level and therefore information on the diversity of this food resource is generally scarce. The aims of this study were: 1) to assess the overall pattern and trends in the use of amphibians as a resource by otters at the range scale, and 2) to highlight current knowledge on the diversity of amphibians taken as prey by otters. Additionally, we carried out osteological identification of amphibian remains in otter spraints (faeces) from southern Italy, with the aim of demonstrating how this method may improve our knowledge on predator–prey relationships. The frequency of occurrence of amphibians in 64 dietary studies averaged 12%. Predation of amphibians by otters increased with longitude and was the highest in the Alpine biogeographical region. Predation by otters was reported on 28 amphibian species (35% of European species). Peaks in their frequency of use were reported for all seasons, mostly in winter and spring. In southern Italy, we identified 355 individuals belonging to at least seven amphibian taxa (64% of available species; Rana italica, Rana dalmatina / italica, Pelophylax kl. bergeri/hispanicus, Hyla intermedia, Bufo bufo, Bufotes balearicus, and Lissotriton italicus ), and pointed out male‐biased predation within the Order Anura (frogs). We conclude that the contribution of amphibians to the richness of the otter's prey community is far higher than commonly perceived, and that osteological analyses allow the detailed investigation of the feeding behaviour of this top predator of freshwater habitats.